Pinned - Martino, Alfred C. (Orlando, Fla. : Harcourt, 2005)
Dealing with family problems, girls, and their own competitive natures, high school seniors Ivan Korske and Bobby Zane face each other in the final match of the New Jersey State Wrestling Championship.
A Junior Library Guild selection.
Ages 12 and up.
2 9 13 28
Keywords: Wrestling -- Fiction; Family problems -- Fiction; Friendship -- Fiction; Competition (Psychology) -- Fiction; New Jersey -- Fiction; Wrestling -- Juvenile fiction; Problem families -- Juvenile fiction; Friendship -- Juvenile fiction; Competition (Psychology) -- Juvenile fiction; New Jersey -- Juvenile fiction